ประสิทธิภาพของพื้นที่ชุ่มน้ำเทียมโกงกางใบใหญ่ในการบำบัดน้ำเสียที่ปนเปื้อนตะกั่วและสังกะสี - พรสุดา ผานุการณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This study evaluated the treatment efficiency of Rhizophora mucronata constructed wetland on wastewater contaminated with Pb and Zn. The synthetic wastewater was dosed with 3 concentration of Pb and Zn, i.e., 5,10 and 20 mg/l each. The synthetic wastewater without Pb and Zn was used as control (control). Wastewater was retained within the system for 3.5 days and left to dry for 3.5 days. The experiment was repeated for 20 times (20 weeks). The results indicated that the highest removal percentage of total nitrogen of wastewater with Pb and Zn 5 mg/l each was 92.57%. The lowest removal percentage of total nitrogen of wastewater with Pb and Zn 20 mg/l each was 90.83%. While, the highest removal percentage of total phosphorus of wastewater without Pb and Zn was 66.33%. The lowest removal percentage of total phosphorus of wastewater with Pb and Zn 20 mg/l each was 37.22%. Whereas, the removal percentage of Pb and Zn of wastewater with Pb and Zn 20 mg/1 each was 94.65% and 93.95%, respectively. After the treatment experiment, soil in experiment sets received wastewater with Pb and Zn 20 mg/l each had the lowest organic matter and nutrients (total nitrogen and total phosphorus) accumulation rate, whereas it had the highest Pb and Zn accumulation rate. The Pb, Zn and nutrients were accumulated higher on surface soil layer (0-5 cm) than the sub soil layer (5-10 cm). At the end of the treatment experiment, nutrient accumulation in leaf tissues received wastewater with Pb and Zn 20 mg/l each had lower total nitrogen than other experiment sets. Furthermore, the results indicated the growth parameter, i.e., stem height and biomass increment rate tended to decreased. The Pb and Zn concentrations in root tissues increased with the increase in wastewater Pb and Zn concentrations. Therefore, the results suggested that the constructed wetland received wastewater with Pb and Zn 20 mg/l each was high effective for removing Pb and Zn from wastewater, whereas the removal percentage of nutrients decreased. Moreover, R. mucronata showed the stem height and biomass increment rate decreased. The results indicated that Pb and Zn exhibit some inhibitory effect on nutrients uptake by R. mucronata. Thus, the optimal condition of constructed wetland planted with mangrove species for treatment of wastewater contaminated with Pb and Zn should be pre-treated before discharging into mangroves in order to prevent the impacts on living organisms.